Indoor Air Concentrations of Heavy Metals in Two Shisha Smoke Cafés in Baghdad - A. F. Al-Easawi, Nada; N. A. Al-Azzawi, Muhammad; H. Afaj, Adnan (Iraqi Journal of Science, 2023)
Shisha smoke represents one of the causes of indoor air pollution. Heavy metals represent the main components in shisha smoke. In this research study, the indoor concentrations of heavy metals in shisha smoke café sites was investigated, samples were taken from two café sites (site1, site 2) which differ in their volume. Site1 volume was 77m3, while site 2 was 437.5m3. Sample were taken by using a low volume sampler (sniffer), and then examined by the Atomic Absorption Spectrometry (AAS). The results showed that indoor air shisha smoke samples for both experimental sites have shown a significant amount of heavy metals as compared with control sampling values. The mean concentration values of (Pb, Zn, Co, Ni, Cr) in site 1 were (11.004, 9.544, 24.088, 19.84, 24.98 μg/m3) respectively, while the mean concentration values of these heavy metal in site 2 were (5.574, 6.578, 16.684, 26.114, 9.636 μg/m3) respectively. Results and conclusions referred those indoor air concentrations during shisha smoking times were high and exceed the WHO standard limits